1995
DOI: 10.1001/jama.1995.03520310056030
|View full text |Cite|
|
Sign up to set email alerts
|

Allele-Specific Chromosome 3p Deletions Occur at an Early Stage in the Pathogenesis of Lung Carcinoma

Abstract: Deletions in the short arm of chromosome 3 occur at the earliest stage (hyperplasia) in the pathogenesis of lung cancer and involve all regions of the respiratory tract. Allele loss is highly specific, but its mechanism remains unknown. Our findings may be of considerable biologic, prognostic, and clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
2
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 253 publications
(101 citation statements)
references
References 25 publications
6
90
2
2
Order By: Relevance
“…We and others have documented this phenomenon (allele speci®c mutations, ASM) previously both in the respiratory epithelium of smokers and in patients with lung cancer (Hung et al, 1995;Kishimoto et al, 1995;Sundaresan et al, 1992;Wistuba et al, 1995). The mechanism by which this phenomenon occurs is unknown.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…We and others have documented this phenomenon (allele speci®c mutations, ASM) previously both in the respiratory epithelium of smokers and in patients with lung cancer (Hung et al, 1995;Kishimoto et al, 1995;Sundaresan et al, 1992;Wistuba et al, 1995). The mechanism by which this phenomenon occurs is unknown.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies of di erent bronchial lesions from the same individual patient demonstrated that at any one locus, loss of parental alleles was not random, and that there was a strong tendency for the identical allele to be lost in all non-neoplastic and neoplastic foci examined (Hung et al, 1995;Kishimoto et al, 1995;Sundaresan et al, 1992;Wistuba et al, 1995) (Figure 1). We refer to this phenomenon as allele speci®c mutations (ASM) (Hung et al, 1995;Kishimoto et al, 1995;Sundaresan et al, 1992;Wistuba et al, 1995).…”
Section: Allele Speci®c Mutations (Asm)mentioning
confidence: 88%
See 3 more Smart Citations